Rudists from the Peña Colorada iron mine and La Minita sulfide deposit, states of Colima and Michoacán, SW Mexico - Rodolfo Corona-Esquivel; Gloria Alencáster (Revista Mexicana de Ciencias Geológicas)
A geological study of the principal mining areas along the Pacific coast in the states of Colima and Michoacán was carried out whit the purpose of understanding the origin of the mineral deposits in southwestern Mexico… in order to continue, download the full paper in PDF.